Which domains of the theoretical domains framework should be targeted in interventions to increase adherence to antihypertensives? A systematic review. Issue 5 (11th February 2022) - Rahman, Murshida; Judah, Gaby; Murphy, Dan; Garfield, Sara F.
Abstract : Nonadherence to antihypertensives is prevalent and is associated with poorer health outcomes. This study aimed to identify psychological factors associated with adherence in patients taking antihypertensives as these are potentially modifiable, and can, therefore, inform the development of effective interventions to increase adherence. PubMed, EMBASE and PsychINFO were searched to identify studies that tested for significant associations between psychological domains and adherence to antihypertensives. The domains reported were categorized according to the Theoretical Domains Framework. The quality of included studies was evaluated using the National Institute for Clinical Excellence critical appraisal of questionnaire checklist. Thirty-one studies were included. Concerns about medicines (a subdomain of 'beliefs about consequences') and 'beliefs about capabilities' consistently showed association with adherence in over five studies. Healthcare professionals should actively ask patients if they have any concerns about their antihypertensives and their belief in their ability to control their blood pressure through taking antihypertensives.